2020
DOI: 10.1002/jcb.29713
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from RPE cells under oxidative stress mediate inflammation and apoptosis of normal RPE cells through Apaf1/caspase‐9 axis

Abstract: This study aims to explore the effects of exosomes, secreted by retinal pigment epithelial (RPE) cells under oxidative stress (OS), on apoptosis and inflammation of normal RPE cells. Exosomes secreted by normal RPE cells (named as exo) and rotenone (2.5 µmol/L) stimulated RPE cells (named as rot-exo) were isolated and extracted by multi-step differential centrifugation for morphology observation under a transmission electron microscopy. pcDNA3.1a, pcDNA3.1a-Apaf1, and p3xFlag-CMV-caspase-9 plasmids were constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…These EVs promoted angiogenesis in endothelial cells [ 208 ]. Another study showed that EVs obtained from RPE cells treated with an oxidative stressor (i.e., Rotenone) caused a reduction in cell proliferation and survival of normal RPE in a dose-dependent manner [ 209 ]. These EVs contained high level of apoptotic protease activating factor 1 (Apaf1) that most likely enhanced the induction of apoptosis and inflammatory response in the normal RPE cells [ 209 ].…”
Section: Evs In Htlv-1-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…These EVs promoted angiogenesis in endothelial cells [ 208 ]. Another study showed that EVs obtained from RPE cells treated with an oxidative stressor (i.e., Rotenone) caused a reduction in cell proliferation and survival of normal RPE in a dose-dependent manner [ 209 ]. These EVs contained high level of apoptotic protease activating factor 1 (Apaf1) that most likely enhanced the induction of apoptosis and inflammatory response in the normal RPE cells [ 209 ].…”
Section: Evs In Htlv-1-related Diseasesmentioning
confidence: 99%
“…Another study showed that EVs obtained from RPE cells treated with an oxidative stressor (i.e., Rotenone) caused a reduction in cell proliferation and survival of normal RPE in a dose-dependent manner [ 209 ]. These EVs contained high level of apoptotic protease activating factor 1 (Apaf1) that most likely enhanced the induction of apoptosis and inflammatory response in the normal RPE cells [ 209 ]. Lastly, Tax has been found to stimulate the production of reactive oxygen species (ROS) in primary human cells resulting in cellular DNA damage and cellular senescence [ 210 ].…”
Section: Evs In Htlv-1-related Diseasesmentioning
confidence: 99%
“…Exosomes derived from ARPE-19 cells under OS regulate Apaf1 expression to increase apoptosis and to induce oxidative injury and inflammatory response through a caspase-9 apoptotic pathway. 172 Collectively, these findings highlight the critical role of exosomes in inflammation and suggest the possibility of utilizing exosomes as an inducer to attenuate inflammation and restore impaired immune responses in various diseases including cancer.…”
Section: Bio-functions Of Exosomesmentioning
confidence: 91%
“…On the other hand, oxidative stress can not only promote the release of exosomes from RPEs, but also make receptor cells engulf exosomes more quickly in the progression of AMD disease ( Nicholson et al, 2020a ; Yang et al, 2020 ). Exosomes under oxidative stress can also increase apoptosis of ARPE-19 cells through overexpression of Apaf1 and induce oxidative damage and inflammation through caspase-9 apoptosis pathway ( Ke et al, 2020 ). In another study exosome from J-cybrids reduced transepithelial resistance (TER) in receptor ARPE-19 cells, and this is associated with high risk of AMD ( Nicholson et al, 2020b ).…”
Section: Exosomes In Retinal Diseasementioning
confidence: 99%